Proceedings of the 1999 Conference on Dissociative Recombination Theory, Experiment, and Applications VI : Stockholm, Sweden, 16-20 June 1999 (World Scientific Publishing Co. Pte Ltd., 2000)
"Dissociative recombination is a complex molecular process that occurs in any plasma cold enough to contain molecular constituents. It is the dominant recombination process in planetary ionospheres and interstellar clouds. In this book, recent developments in the fields of molecular ion physics, atomic and molecular theory, astrochemistry, aeronomy and plasma physics are discussed."--Publisher's website